ENHANCING FINANCIAL BEHAVIOR THROUGH FAMILY FINANCIAL LITERACY AND KNOWLEDGE: EVIDENCE FROM PLS-SEM ANALYSIS - Ahmad Yuni Prasetio Mahfud Ahmad; Tri Murwaningsih; Leny Noviani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the effect of family financial literacy on financial behavior, both directly and indirectly through financial knowledge as a mediating variable, among Grade 12 students at SMAN 1 Jogonalan, Klaten Regency. The research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) and involved respondents representing individuals who experienced financial socialization within their family environment. The results reveal that family financial literacy has a significant direct effect on financial behavior, with a path coefficient of 0.292 and a p-value of 0.000. The 95% confidence interval (0.154–0.462) and the effect size (f² = 0.178) indicate a moderate influence. Furthermore, family financial literacy significantly affects financial knowledge, evidenced by a path coefficient of 0.556 and a p-value of 0.000, with an effect size of 0.447 categorized as moderate. Financial knowledge also shows a strong and significant effect on financial behavior, with a path coefficient of 0.619, a p-value of 0.000, an effect size of 0.881, and a 95% confidence interval (0.461–0.722). Additionally, financial knowledge significantly mediates the relationship between family financial literacy and financial behavior, as indicated by an indirect effect of 0.334 and a p-value of 0.000. These findings highlight the essential role of family-based financial literacy in improving individuals’ financial knowledge and financial behavior. The study contributes to the theoretical development of financial literacy literature and offers practical implications for families, educational institutions, and policymakers in strengthening family-centered financial education programs.